2020
DOI: 10.31018/jans.v12i4.2426
|View full text |Cite
|
Sign up to set email alerts
|

Trend of studies on carbon sequestration dynamics in the Himalaya hotspot region: A review

Abstract: The present communication deals with the carbon dynamics in the Himalaya hotspot region. The Himalaya, a mountain range shared by Pakistan, India, Nepal, Bhutan and Myanmar, is one of the biologically richest regions in the world that play an important role as source and sink in global carbon cycle. The purpose of this paper was to review and provide available studies related to carbon sequestration in the Himalayas. The carbon in forest is stored in five different pools viz. above-ground biomass, below-ground… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 95 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…The total of aboveground biomass and carbon in conifer forests with a diameter of (60-80) was typically high in India, with 85.4 t/ha (Table 3). It was further supported by data provided by [59] in the Nainital area of Uttarakhand, where research was conducted on the entire biomass of tree species and the highest carbon stock was reported to have been shared by conifer forest. In chir pine or conifer forest, the presence of Quercus species has provided more carbon [60,61] on the other hand, found that tree density and diameter did not affect the aboveground carbon stock of diverse tree species in the Cachar forest [62].…”
Section: Comparisons Of Carbon Stock Of Three Himalayan Countries (Nepal Bhutan and India)mentioning
confidence: 70%
See 1 more Smart Citation
“…The total of aboveground biomass and carbon in conifer forests with a diameter of (60-80) was typically high in India, with 85.4 t/ha (Table 3). It was further supported by data provided by [59] in the Nainital area of Uttarakhand, where research was conducted on the entire biomass of tree species and the highest carbon stock was reported to have been shared by conifer forest. In chir pine or conifer forest, the presence of Quercus species has provided more carbon [60,61] on the other hand, found that tree density and diameter did not affect the aboveground carbon stock of diverse tree species in the Cachar forest [62].…”
Section: Comparisons Of Carbon Stock Of Three Himalayan Countries (Nepal Bhutan and India)mentioning
confidence: 70%
“…This conclusion is similar to the findings of [90] who observed that SOC stocks altered predictably with elevation. Since there is little literature from Bhutan on carbon stock (3 percent publication), there is no precise data from Bhutan on carbon stock in previous years, as stated by [59] As a result, it is not included in this part.…”
Section: Fig 2 Carbon Stocks Along An Altitudinal Gradient In Bhutanmentioning
confidence: 99%
“…The Indian Himalayan region (IHR), a biodiversity hotspot, is home to varied species of flora and fauna and provides numerous ecosystem services (Negi et al, 2019;Ahirwal et al, 2021) such as carbon sequestration, water regulation and livelihood to a million of people. Considering its vast natural wealth and unique environmental conditions, IHR is reported to sequester 65 million tonnes of carbon annually (Tolangay and Moktan, 2020) and possess more significant climate change mitigation potential. In this context, the Central and Western Himalaya has been investigated extensively for biomass and carbon stock estimation (Sharma et al, 2010(Sharma et al, , 2016(Sharma et al, , 2018Gairola et al, 2011;Dar and Sundarapandian, 2015;Dar et al, 2017;Kaushal and Baishya, 2021;Dar and Parthasarathy, 2022;Haq et al, 2022;Tiwari et al, 2023).…”
mentioning
confidence: 99%
“…The forests of the Himalayan region are a hotspot of biodiversity which provide vital ecosystem services and products (Negi et al, 2019). The forest of the Indian Himalayan region (IHR) sequesters around 65 million tonnes of carbon annually (Tolangay & Moktan, 2020) thus playing a vital role in regulating climate. Specifically, the Himalayan forests have drawn the attention of researchers because of their unique position within the global vegetation pattern.…”
mentioning
confidence: 99%